(untitled) (Revista Educação, Artes e Inclusão, 2021)
This study aims to report a work with seven deaf students of the 4th year of a elementary school, with proposal for bilingual education, in a city in the western Paraná. Concept Maps were used in that school as a methodological approach, based on David Ausubel’s Meaningful Learning Theory. In order to comply with the contents present in the school’s Pedagogical Political Project, the main teacher, who works in an interdisciplinary way the subjects of Portuguese, Mathematics, History, Geography, Sciences and Religious Education, sought themes that could be generators of content learning. that should be explored in each subject. From the generative theme "Healthy Eating - Food Pyramid" set for the development of activities that encompassed more broadly selected content, began to organize activities and materials that would be used to facilitate the learning of the theme.In this study, Concept Maps proved to be an important methodological approach that contributes to Meaningful Learning and assisted deaf students in understanding concepts, especially the visual potential they offer.